Evaluation Analysis of Environmentally Based Sustainable Management at Dago Dreampark Bandung - Gani, Davin; Sofiani (Media Wisata, 2024)
This research aims to analyze the environmental management of destinations carried out at Dago Dreampark so that tourist destinations remain maintained and protected. Evaluation of sustainable management carried out regularly is needed so that factors can always be monitored that can cause a decline in the natural environment and natural resources owned by tourist destinations, along with planning & monitoring efforts made to overcome these factors. The method that will be used in this research is a descriptive qualitative method. Data collection will be carried out using the tourist destination photo/video documentation method, direct observation of the sustainable development of the Dago Dreampark Bandung, and using the direct interview method with the Tourism Destination Management. The results of this research reveal the applications used by Dago Dreampark in managing destinations sustainably, starting from waste management, air and water management, and also managing nature conservation at Dago Dreampark. This research provides knowledge about the effectiveness of sustainable management applied to tourist destinations.